The influence of ylang-ylang flower extract administration (Cananga Odorata) as an Aedes Aegypti Mosquito Instar III - Devi Nadila, Eka; Risma, Risma; Suriyanto, Adi (Science Midwifery, 2024)
The dengue virus is spread by the Aedes aegypti mosquito. In Indonesia, dengue hemorrhagic fever (DHF) still has a relatively high morbidity and fatality rate. Therefore, initiatives are required to reduce the incidence by controlling mosquito populations, using natural larvicides as one method. Ylang-ylang flower (Cananga odorata) is among the vegetation that may be used as larvicides because it contains flavonoids, saponins, tannins, linalool, and eugenol. This study aims to investigate the impact of administering ylang-ylang flower extract (Cananga odorata) as larvae of Aedes aegypti mosquito instar III. This work used a post-test only control group experiment conducted in a laboratory experimental at the Entomology Laboratory of the Institute of Tropical Disease (ITD) Airlangga University. There were six research groups used in this study, namely negative control, the control using ylang-ylang flower extract concentration with 0,1%; 0,75%; 1,5%; 2,25%, and 3%. The data analysis using larval samples were obtained from the Institute of Tropical Disease (ITD) Airlangga University. According to the analysis, a level of 3% the highest average mortality or death of larvae was 100%, and the lowest average death of larvae at a concentration of 0,1% was 3,75%. The Kruskal-Wallis test findings revealed substantial variations (p<0.05) in each group, and the Mann Whitney U post hoc test revealed a substantial variations in concentrations of 0,1% with 0,75%; 1,5%; 2,25%; 3% and concentrations between 0,75% to 1,5%, 2,25%, and 3%. Considering the findings of the study, it can be determined that the ylang-ylang's flower extract (Cananga odorata) has an influence as a natural larvicide of Aedes aegypti mosquitoes instar III.